Everything else in the universe - Holczer, Tracy (G.P. Putnam's Sons, 2018)
"In 1971, twelve-year-old Lucy Rossi's dad returns from Vietnam after losing part of his arm, and her whole family must learn to adjust to a new dynamic, but Lucy's friend Milo unknowingly helps her navigate through this difficult time of fear and uncertainty to realize she is much tougher than she thought"--Provided by publisher.